CREATIVITY AND INNOVATION: THE ROLE OF ORGANIZATIONAL CULTURE IN STARTUP COMPANIES - Setyowati Subroto; Livia Alves; Rafaela Lima (Yayasan Adra Karima Hubbi, 2025)
In today’s dynamic business environment, startup companies are increasingly recognized for their ability to innovate and drive creativity. Organizational culture plays a critical role in shaping these qualities, fostering an environment where employees feel encouraged to think outside the box. However, the specific ways in which organizational culture influences creativity and innovation within startups remain underexplored, particularly in small and emerging companies. This study aims to explore the role of organizational culture in fostering creativity and innovation within startup companies. By examining the interplay between organizational culture and creative processes, this research seeks to provide insights into how startups can cultivate a culture that drives innovation and long-term success. A mixed-method approach was employed, consisting of qualitative interviews with founders and employees of 15 startups and quantitative surveys distributed to 100 startup employees. The research focused on three key aspects of organizational culture: values, leadership, and communication. Data was analyzed using thematic analysis for qualitative responses and statistical analysis for survey results. The study revealed that a flexible, open, and collaborative organizational culture significantly enhances creativity and innovation. Startups that prioritized trust, autonomy, and transparent communication reported higher levels of employee satisfaction and more innovative output.